Treatment Strategies and Outcomes of Symptomatic Spontaneous Isolated Superior Mesenteric Artery Dissection: A Systematic Review and Meta-analysis. (October 2018) - Zhu, Yating; Peng, Yanghong; Xu, Mingyue; Wei, Yingqi; Wu, Shanshan; Guo, Wei; Wu, Zhongyin; Xiong, Jiang
Purpose: To analyze the published treatment experience with symptomatic spontaneous isolated superior mesenteric artery dissection (SISMAD).Methods: A literature search of the PubMed and Cochrane databases was conducted for articles on symptomatic SISMAD published in English from January 2007 to January 2018. Case series reporting on both treatment modalities and outcomes were included, while those on traumatic or iatrogenic SMA dissection or SMA dissection accompanied by aortic or other visceral artery dissection were excluded. Overall event rates for treated symptomatic SISMAD were calculated using pooled analyses. The rate of initial conservative treatment, the success rate, the rate of conversion to intervention, and the failure rate in patients with vs without antithrombotic therapy were calculated for each study and compared using a meta-analysis of proportions.Results: The 25 articles selected encompassed 616 SISMAD cases, of which 514 were symptomatic cases eligible for the analysis. Among the latter, initial treatment consisted of conservative therapy in 447 (87.0%) patients and surgical interventions in 67 (13.0%) patients [45 (8.7%) endovascular procedures and 22 (4.3%) open surgeries]. Among conservative cases, 238 (53.2%) received antithrombotic therapy while 172 (38.5%) did not; 50 (11.2%) cases were converted to intervention [42 (84%) endovascular]. Conservative treatment was initially used in 85.2% of pooled cases with an 84.7% success rate, a 14.3% rate of conversion to intervention, and conservative treatment failure rates of 17.8% and 10.1% in patients treated with vs without antithrombotic therapy, respectively (p=0.103).Conclusion: Conservative treatment appeared safe and effective in >80% of symptomatic SISMAD cases, without apparent benefit for antithrombotic agent use. Initial or secondary intervention was more often endovascular, with favorable success rates and short-term outcomes. Large, prospective randomized trials with long-term follow-up are warranted on the treatment for symptomatic SISMAD.